Intrahepatic cholestasis of pregnancy: diagnosis and management; a survey of Royal Australian and New Zealand College of Obstetrics and Gynaecology fellows. (8th February 2014) - Arthur, Chris; Mahomed, Kassam
<x xml:space="preserve">Abstract</x> Background Intrahepatic cholestasis of pregnancy (ICP) is an uncommon obstetric condition characterised by intense maternal pruritis and biochemical abnormality. There is a degree of contention regarding the diagnosis and management of ICP, and currently, there are no nationally accepted guidelines. Aims To conduct a survey of Fellows and Members of the Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) regarding their diagnosis and management ICP. Methods An online survey of currently practising RANZCOG Fellows and Members, utilising Survey Monkey. Results Thirty percent of those sent the survey responded, comprising approximately 40% of practising obstetricians. Fasting bile acid and serum transaminase elevation in association with the characteristic itch define the disease process for the majority of respondents and also inform management decisions. There was no critical level of bile acid elevation that mandated treatment for the majority of respondents. Nearly 90% of respondents induce women with ICP at 37–38 completed weeks of pregnancy, due to concerns regarding possible fetal demise. About one‐third of respondents refer to the Royal College of Obstetricians and Gynaecologists (RCOG) Green‐top Guideline to advise their decision‐making process, and a similar proportion use local or hospital‐based guidelines. Conclusions Elevated fasting bile acids and abnormal liver function tests define the diagnosis and inform management of ICP by Australian obstetricians. Routine induction of labour for patients with ICP at 37–38 completed weeks of pregnancy is widely practised in Australia. An evidence‐based guideline would assist clinicians who manage such cases in Australia.